1992
DOI: 10.1007/bf01745863
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a high dose of ascorbate on ischemia-reperfusion-induced mitochondrial dysfunction in canine hearts

Abstract: The cardioprotective effects of a high dose of ascorbate on ischemia-reperfusion-induced myocardial damage were investigated using open chest anesthetized dogs. Two-hour occlusion of the left anterior descending coronary artery (LAD) induced mitochondrial dysfunction with a depletion of mitochondrial glutathione (GSH) concentration. Two-hour LAD occlusion followed by 1-h reperfusion worsened the ischemia-induced mitochondrial dysfunction together with a marked depletion of mitochondrial GSH concentration. Asco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 23 publications
1
13
0
1
Order By: Relevance
“…2 Instead, electron flow through the ETC upon reperfusion was described as a source of potentially detrimental reactive oxygen species (ROS), proposed to trigger ischaemia-reperfusion (I/R) injuries. 2 Conversely, the therapeutic use of untargeted antioxidants such as vitamin C for post-ischaemic cardioprotection has given contradictory results, [4][5][6][7][8][9] and itself produced detrimental side effects when therapeutically used. 10 These seemingly contradictory results were thought to be due to biphasic effects of ROS with high ROS concentrations leading to damage and lower concentrations eliciting adaptive responses.…”
Section: Introductionmentioning
confidence: 99%
“…2 Instead, electron flow through the ETC upon reperfusion was described as a source of potentially detrimental reactive oxygen species (ROS), proposed to trigger ischaemia-reperfusion (I/R) injuries. 2 Conversely, the therapeutic use of untargeted antioxidants such as vitamin C for post-ischaemic cardioprotection has given contradictory results, [4][5][6][7][8][9] and itself produced detrimental side effects when therapeutically used. 10 These seemingly contradictory results were thought to be due to biphasic effects of ROS with high ROS concentrations leading to damage and lower concentrations eliciting adaptive responses.…”
Section: Introductionmentioning
confidence: 99%
“…Ascorbate is known to have a multiplicity of antioxidant properties, including the ability to act as a reducing agent to scavenge free radicals directly, and sparing other antioxidants, such as ␣-tocopherol (vitamin E) and GSH (35,42). Furthermore, a previous study has shown that administration of high-dose ascorbate attenuates myocardial I/R injury and mitochondrial dysfunction, suggesting an antioxidant action localized at or near the mitochondrial compartment (40). Based on studies demonstrating similar antioxidant actions and a mutual sparing effect between GSH and ascorbate (37,57), there appears to be some functional redundancy between these two antioxidant systems.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports showing a close correlation between the production of ROS and simultaneous consumption of endogenous antioxidants 151,152 . Indirect evidence consistent with this view is the cardioprotective effects of free radical scavengers and antioxidant supplements 161,162,163 . New research finds that rats given oral low dose of quercetin significantly protected against the injury that normally occurs during ischemia and reperfusion 164 .…”
mentioning
confidence: 82%